- Effects of Reishi Mushroom (Ganoderma Lucidum) Powder Inclusion into Quail Diets on Animal Performance, Carcass Traits, Intestinal Microflora and Serum Parameters - Ulger, İ and Kaliber, M and Hizlisoy, H and Ayasan, T (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was carried out to determine the effects of reishi mushroom (Ganoderma lucidum) powder inclusion into quail diets on live weight, live weight change, feed consumption, feed conversion ratio, carcass traits, intestinal microflora and serum biochemical parameters of the animals. Dietary reishi mushroom (RM) addition did not influence live weight changes of the treatment groups (P> 0.05). Weekly and overall feed consumptions of the treatment groups were not influenced by RM supplementations (P> 0.05). There were not any significant differences in feed conversion ratios of the treatment groups (P>0.05). Dietary RM inclusion did not affect the overall carcass parameters (P> 0.05). The differences in intestinal bacteria populations of the treatment groups were not found to be significant (P> 0.05). Also, there were not any significant differences in blood serum total cholesterol, glucose, total protein and triglyceride levels of the treatment groups (P> 0.05). It was concluded that dietary RM inclusion into animal diets had a little effect on performance and carcass traits of Japanese quail. But there were slight improvements in some parameters due to antioxidant and antimicrobial effects of reishi mushroom. Further research is recommended to be conducted with greater ratios of dietary RM and with different poultry species.